The early Renaissance and vernacular culture - Dempsey, Charles (The Bernard Berenson lectures on the Italian Renaissance, 2012)
List of illustrations -- Introduction -- Courtly lyric I. Simone Martini, French courtly lyric, and the vernacular -- Courtly lyric II. Sandro Botticelli and Poliziano : humanist learning and the vernacular -- Civic ritual I. Cardinal Orsini's paintings and Baccio Baldini's engravings of the Sibyls : humanist learning and vernacular drama -- Civic ritual II. Reconstructing the vernacular octaves with the prophecies of the twelve Sibyls -- Appendix. Cardinal Orsini's twelve Sibyls and their prophecies in vernacular octaves reconstructed.